Challenges and Impacts behind the Recognition of the Customary Law People of Enggano Island - Hariawan, Muhamad Arby (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2025)
This study aims to analyze the challenges and implications surrounding the legal recognition of the Enggano Tribe as a Customary Law Community (Masyarakat Hukum Adat) on Enggano Island, Bengkulu Province, Indonesia. The recognition is rooted in the community’s unique cultural identity, the urgency to preserve indigenous traditions, and the necessity to institutionalize their legal status within the national legal framework. Employing a descriptive qualitative approach, data were collected through in-depth interviews, focus group discussions (FGDs), literature review, field observation, and documentation. Informants were selected purposively and included tribal leaders, village heads, local government officials, and representatives of civil society organizations. The findings reveal three key challenges: (1) power dualism between customary structures and village governance; (2) limited horizontal support from other indigenous groups in Bengkulu; and (3) lack of administrative documentation, particularly in relation to customary history and territorial boundaries. The legal recognition of the Enggano people carries significant implications, including the protection of local culture, strengthening of traditional identities, and sustainable management of natural resources based on indigenous wisdom. This study recommends fostering reconciliation between tribal and formal authorities, drafting inclusive and culturally sensitive regulations, and implementing participatory mapping to support the legal standing of the Enggano community as an indigenous legal entity